Is Equity Premium a Puzzle in the Czech Republic - Blaščík, Adam; Potužák, Pavel; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
In this thesis I address the equity premium puzzle in the Czech Republic on both, the- oretical and empirical grounds. The equity premium puzzle states that the di erence between returns on risky and risk free asset is too high to be explained by meaningful coe cient of risk aversion. Risk aversion needed to justify the data would be too high and therefore incompatible with the microeconomic evidence. I review the literature on this phenomenon, especially regarding di erent e orts to explain the puzzle. I use Czech data from period between 1996 to 2016 on stock index returns, government bonds and per capita consumption and two di erent modeling approaches to estimate the coe cient of relative risk aversion. I follow the modeling strategy of Mehra & Prescott (1985) and use adjusted model as a robustness check. The main nding is that in the observed period the risk aversion coe cient is less extreme than suggested by Mehra & Prescott, but still too high to justify the observed risk premium. On top of that results for the Czech data are unstable over time.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses